The relationship of age when motor alignment is achieved and the subsequent development of stereopsis in infantile esotropia - ÇERMAN, EREN; ERASLAN, MUHSİN (MOSBY-ELSEVIER, 2014)
PURPOSE To determine the oldest age beyond which the chance of developing stereopsis is not possible even with excellent motor alignment in patients with infantile esotropia. METHODS The medical records of children with infantile esotropia who underwent a single operation and had alignment within 10(Delta) of orthotropia at all follow-up examinations were retrospectively reviewed. Patients were assessed for stereopsis after the age of 48 months. RESULTS A total of 38 children were included. There was a statistically significant inverse correlation between age at surgery and final stereopsis (r = 0.494, P = 0.002). There was a significant difference at mean age at surgery between patients having stereopsis better than 1000 arcsec and those having no stereopsis (P = 0.002). Post hoc power analysis revealed a value of 85%. Receiver operating characteristic curve analysis revealed that the optimum cut-off value of the age at surgery for predicting stereopsis was 16 months (Youden index = 0.474; area under ROC curve, 0.784; 95% CI: 0.62-0.90; P = 0.0002). CONCLUSIONS Surgery for infantile esotropia is most likely to result in measureable stereopsis if patient age at alignment is not more than 16 months.
Keywords: STEREOACUITY OUTCOMES; SURGICAL ALIGNMENT; SURGERY; ACUITY